Rancang Bangun Website Layanan Muggle Cloud Terintegrasi dengan WHMCS & Tidio LiveChat - Permatasari, Wulan; Septanto, Henri (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2024)
This study aims to design and develop the Muggle Cloud service website integrated with WHMCS (Web Host Manager Complete Solution) and Tidio LiveChat. The background of this research is the need for a hosting platform that can manage hosting services, payments, and customer support effectively and efficiently. Many hosting companies currently face difficulties in integrating account management systems, payment processes, and customer support, resulting in suboptimal services for users. The purpose of this research is to develop an integrated system that can solve these problems by providing a website that facilitates hosting service management and supports real-time interaction between customers and technical support. The method used in this research is the Waterfall software development model, which includes the stages of requirement analysis, system design, implementation, testing, and maintenance. Data were collected through literature studies, interviews with related parties, and analysis of existing systems. The results of the research show that the integration between WHMCS and Tidio LiveChat on the Muggle Cloud platform successfully provides an effective solution for managing hosting services and customer support. The implementation of this system not only simplifies administrative and payment processes but also increases responsiveness to customer needs and inquiries through live chat features. The conclusion of this research is that the integrated system can improve operational efficiency and customer satisfaction in hosting service companies and make an important contribution to the development of integrated hosting service management technology.